The Effectiveness of Tepid Sponge Therapy in Managing Hyperthermia among Patients with Typhoid Fever in the Emergency Department - Ibna Humrah; Haeril Amir; Rahmat Hidayat; Safruddin Safruddin (An Idea Nursing Journal, 2025)
Typhoid fever is an acute infectious disease caused by Salmonella enterica serovar Typhi (S. typhi), which primarily affects the human digestive system. It is transmitted through the consumption of food or water contaminated with the feces or urine of infected individuals, and can also spread through direct contact with bacterial carriers. One effective solution to reduce body temperature in patients with typhoid fever is the application of tepid sponge therapy, a non-pharmacological nursing intervention used to alleviate hyperthermia. This study aims to describe the application of water tepid sponge therapy in lowering body temperature among patients with typhoid fever. The results showed that after the implementation of tepid sponge therapy, the patient’s body temperature decreased from 39°C to 37.8°C, indicating the effectiveness of this therapy in reducing fever. In conclusion, tepid sponge therapy has a significant effect on lowering body temperature in patients with typhoid fever. It is expected that this finding can serve as a useful reference for improving nursing care, particularly for patients suffering from typhoid fever.